Elevated SAMD3 expression in T cells predicts improved survival in pancreatic ductal adenocarcinoma patients - Lingyi Fu; Enliang Zhou; Shuo Li; Ziteng Li; Liyan Wu; Xinxin Zhou; Lang Tian; Bokang Cui (Cancer Immunology, Immunotherapy)
Abstract Objective Pancreatic ductal adenocarcinoma (PDAC) has an immune-suppressive tumor microenvironment that contributes to resistance to immunotherapy. This study aimed to demonstrate that elevated sterile alpha motif domain-containing protein 3 (SAMD3) expression in effector CD8+ T cells was associated with improved survival in PDAC patients. Design We investigated the heterogeneity and gene expression profiles of T cells using a single-cell RNA sequencing (sc-RNA-seq) dataset comprised of human PDAC samples. SAMD3 mRNA expression was further evaluated in a tumor-specific OT-I/ovalbumin (OVA) mouse model. SAMD3 levels and their clinical significance were evaluated via immunohistochemistry (IHC) analysis. Results SAMD3 was highly expressed in cytotoxic CD8+ T cells, with expression significantly downregulated during T cell exhaustion. SAMD3 levels were positively correlated with CD8+ T cell function. In PDAC patients, high SAMD3 levels in T cells were associated with improved overall survival (OS), disease-free survival (DFS), and T cell infiltration. A patient exhibiting partial response to combination immunotherapy also showed high SAMD3 levels in T cells. Conclusion SAMD3 is a biomarker of T cell function, with elevated expression in T cells predicting improved survival. These findings highlight the potential of precision immunotherapy approaches for treating PDAC.